Modernizing Testing: A Comparative Review of Test Automation Frameworks and AI Tools - Sothy Sundara, Raju; Wai Yie, Leong (INTI International University, 2025)
Artificial Intelligence has emerged as a revolution in software testing due to the software industry’s rapid expansion, allowing Quality Assurance (QA) teams to produce higher-quality software more quickly and effectively. The comparative assessment of test automation frameworks and Artificial Intelligence (AI) powered tools presented in this journal emphasises the revolutionary potential of incorporating advanced AI capabilities into software testing procedures. The objective of this study is to create a framework that will enable organisations to implement AI-driven automation in software testing that is compatible with their requirements. The expected results from this research are to come up with a framework that improves accuracy, scalability, and adherence to software standards while minimizing manual effort and increasing overall testing efficiency. The methodology combines questionnaires and a literature review to discover the organisation’s automation technologies and their influence on increasing product quality. A hybrid methodology will be used for this study that will have both quantitative and qualitative data via surveys and interviews review to discover the organisation’s automation technologies and their influence on increasing product quality.